1974
DOI: 10.1126/science.183.4123.419
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cellular Mediated Immunity in Marihuana Smokers

Abstract: The cellular mediated immunity of 51 young chronic marihuana smokers. as evaluated by the lyomphocyte response in vitro to allogeneic cells and to phytohemagglutinin, was significantly decreased and similar to that of patients in whom impairment of T (thymus derived) cell immunity is known to occur. This inhibition of blastogenesis might be related to an impairment of DNA synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
2

Year Published

1974
1974
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(54 citation statements)
references
References 11 publications
1
51
0
2
Order By: Relevance
“…Studies in the early 1970s using human peripheral blood mononuclear cells (PBMCs) from marijuana smokers showed a tendency for heavy use to result in suppression of lymphocyte proliferation in culture as well as alterations in PBMCs immune cell subsets (154). Serum immunoglobulin (Ig) levels were also modulated by marijuana use, with IgG protein levels decreasing and IgE protein levels increasing.…”
Section: Marijuana-induced Enhancement Of Susceptibility To Infectionmentioning
confidence: 99%
“…Studies in the early 1970s using human peripheral blood mononuclear cells (PBMCs) from marijuana smokers showed a tendency for heavy use to result in suppression of lymphocyte proliferation in culture as well as alterations in PBMCs immune cell subsets (154). Serum immunoglobulin (Ig) levels were also modulated by marijuana use, with IgG protein levels decreasing and IgE protein levels increasing.…”
Section: Marijuana-induced Enhancement Of Susceptibility To Infectionmentioning
confidence: 99%
“…The increase was abrogated by SR144528, L-NAME, indomethacin, and rofecoxib. Our results suggest that 2AG and CP55,940 decreased mast cell activation in a manner that is susceptible to a CB 2 receptor antagonist and to inhibition of nitric oxide and prostanoid pathways.The immunosuppressive effect of tetrahydrocannabinol (THC) was formerly reported both in humans (Nahas et al, 1974) and experimental animals (Coffey et al, 1996). More recently, the effects of THC on human immune functions and host defense have been reviewed, providing evidence that THC can suppress the human immune response in a host of leukocyte subsets and alveolar macrophages, further stressing the relationship between marijuana smoking and immunologically-related diseases (Klein et al, 1998).…”
mentioning
confidence: 99%
“…3,4 In addition, we found an upregulation of hepatic CB2 receptor but not CB1 receptor expression in a mouse model of CCl 4 -induced hepatic fibrosis (Fig. 1).…”
Section: Potential Role Of Cb2 Receptors In Cannabis Smokers With Chrmentioning
confidence: 81%
“…Indeed, we previously showed by both RT-PCR and immunohistochemistry that CB1 and CB2 receptors are markedly upregulated in human liver samples with cirrhosis compared with normal liver, predominantly in hepatic myofibroblasts. [2][3][4] In addition, we found that CB1 knockout (KO) mice showed reduced liver fibrosis following chronic CCl4 intoxication, an effect related to reduced accumulation of hepatic myofibroblasts (Grenard et al 2 and Teixeira-Clerc et al, personal results). These results therefore strongly suggest that activation of CB1 receptors enhances liver fibrogenesis.…”
Section: Replymentioning
confidence: 98%